"Our services are not the same": the impact of the COVID-19 pandemic on care interactions in women's shelters - Caitlin Burd; Isobel McLean; Jennifer C. D. MacGregor; Tara Mantler; Jill Veenendaal; C. Nadine Wathen (BMC, 2023)
Abstract Background Guidelines and regulations in response to the COVID-19 pandemic have significantly impacted the health care sector. We explore these impacts in the gender-based violence (GBV) services sector and, more specifically, in the context of women's shelters. Methods Using an interpretive description and integrated knowledge mobilization approach, we interviewed 8 women's shelter clients, 26 staff, and conducted focus groups with 24 Executive Directors. Results We found that pandemic responses challenged longstanding values that guide work in women's shelters, specifically feminist and anti-oppressive practices. Physical distancing, masking, and closure of communal spaces intended to slow or stop the spread of the novel coronavirus created barriers to the provision of care, made it difficult to maintain or create positive connections with and among women and children, and re-traumatized some women and children. Despite these challenges, staff and leaders were creative in their attempts to provide quality care, though these efforts, including workarounds, were not without their own challenges. Conclusions This research highlights the need to tailor crisis response to sector-specific realities that support service values and standards of care.